2012
DOI: 10.1007/s00228-012-1283-9
|View full text |Cite
|
Sign up to set email alerts
|

Non-steroidal anti-inflammatory drugs (NSAIDs) and hypertension treatment intensification: a population-based cohort study

Abstract: Exposure to NSAIDs leads to an intensification of hypertension treatment, especially in patients treated with ACEIs or ARBs. Renin-angiotensin system blockers should be avoided whenever NSAIDs are prescribed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 30 publications
0
25
0
3
Order By: Relevance
“…In contrast, NSAIDs do not interact with CCBs and CAAs whose actions are apparently unrelated with renal/extrarenal production of prostaglandin31. The mechanism of action (MOA) has also been verified by a recent large-scale clinical study32.…”
Section: Resultsmentioning
confidence: 76%
“…In contrast, NSAIDs do not interact with CCBs and CAAs whose actions are apparently unrelated with renal/extrarenal production of prostaglandin31. The mechanism of action (MOA) has also been verified by a recent large-scale clinical study32.…”
Section: Resultsmentioning
confidence: 76%
“…A recent study analyzing 2680 hypertensive patients concomitantly treated with NSAIDs or acetaminophen demonstrated that NSAID use, particularly ibuprofen, was associated with a small increase in systolic blood pressure [62]. To evaluate the impact of NSAID therapy on hypertension and the need for hypertension treatment intensification, Fournier et al conducted a cohort study involving 5710 hypertensive subjects with a follow-up of about 4 years, demonstrating that exposure to NSAIDs, particularly diclofenac and piroxicam, led to intensification of treatment of hypertension, especially in patients treated with angiotensin converting enzyme inhibitors or angiotensin receptor blockers [63]. Furthermore, hypertensive patients are often treated with diuretics and angiotensin converting enzyme inhibitors or angiotensin receptor blockers, and it has been previously demonstrated from a UK database of 487,372 patients treated with antihypertensive therapies that NSAIDs' addition to this double therapy significantly increased the risk of renal complications and acute kidney injury [64].…”
Section: Nsaids and Hypertensionmentioning
confidence: 98%
“…This is mediated through the inhibition of the production of vasodilatory prostanoids in the kidneys, thereby inducing vasoconstriction of afferent renal arterioles, fluid retention, and reduction in renal blood flow, promoting activation of the rennin–angiotensin system [2]. Although a well-designed trial, adjusting for drug exposure and comparing the hypertensive effects of NSAIDs, has not been conducted to date, a retrospective study reported that ibuprofen appears to be less likely than diclofenac and piroxicam to necessitate an intensification of antihypertensive treatment [86]. …”
Section: Pharmacodynamicsmentioning
confidence: 99%